Assessing the cost-utility of preferentially administering Heplisav-B vaccine to certain populations. Issue 51 (3rd December 2020) - Rosenthal, Elizabeth M.; Hall, Eric W.; Rosenberg, Eli S.; Harris, Aaron; Nelson, Noele P.; Schillie, Sarah
Highlights: Heplisav-B's shortened dosing schedule is advantageous for high risk populations. Heplisav-B results in decreased HBV-related morbidity and mortality. Heplisav-B is cost-saving vs Engerix-B in adults with diabetes, obesity, CKD, HIV; older adults, PWID. Abstract: Vaccination is the primary strategy to prevent hepatitis B virus (HBV) infection in the United States. Prior to 2017, most standard hepatitis B vaccine schedules required 3 doses over 6 months. Heplisav-B, approved in 2017, is administered in 2 doses over a 1 month time period but has a higher per-dose cost ($115.75 per dose compared to $57.25 per Engerix-B dose, costs as of June 1, 2019). We aimed to assess the cost-utility of providing the two-dose Heplisav-B vaccine compared to a three-dose Engerix-B vaccine among adult populations currently recommended for vaccination against hepatitis B. We used a decision-tree model with microsimulation and a Markov disease progression process to assess the cost-utility separately for the following populations: adults with diabetes, obesity, chronic kidney disease, HIV; non-responders to previous hepatitis B vaccination; older adults; and persons who inject drugs (PWID). We modeled epidemiologic outcomes (incident HBV infections, sequelae and related deaths), costs (2019 USD) and benefits (quality-adjusted life years, QALYs) and compared them across strategies. Sensitivity analyses assessed the cost-utility at varying estimates of Heplisav-B efficacy. In the base case scenario for each population, vaccination with Heplisav-B resulted in fewer HBV infections (37.5–59.8% averted), sequelae, and HBV-related deaths (36.3–71.4% averted). Heplisav-B resulted in decreased costs and increased benefits compared to Engerix-B for all populations except non-responders. Incremental costs from the baseline strategy ranged from $4746.78 saved (PWID) to $14.15 added cost (non-responders). Incremental benefits per person ranged from 0.00005 QALYs (older adults) to 0.7 QALYs (PWID). For persons with HIV and PWID, Heplisav-B resulted in lower costs and increased benefits in all scenarios in which Heplisav-B series efficacy was at least 80%. Vaccination using Heplisav-B is a cost-saving strategy compared to Engerix-B for adults with diabetes, chronic kidney disease, obesity, and HIV; older adults; and PWID.